An investigation into the physical determinants of change of direction speed - Jones, P.; Bampouras, T.; Marrin, K. (The Journal of Sports Medicine and Physical Fitness, 2009)
Aim. Change of direction speed (CODS) is an important attribute for many sports and is believed to be influenced by a variety of physical factors. However, there is a lack of consensus as to which physical attributes relate to CODS. The aim of this study was to examine the relationship of several physical attributes to CODS. Methods. Thirty-eight subjects (mean±SD: age, 21.5±3.8 years; height, 1.77±0.07 m; mass, 77.5±13.9 kg) undertook tests of speed, CODS, strength and power. Running speed was assessed via a 25 m sprint with split times taken at 5, 20 and 25 m. CODS was assessed by a 505-test, which involves measuring the time to complete a 5 m out and back course. The strength and power tests included unilateral isokinetic concentric and eccentric knee extensor and flexor strength at 60°/s and bilateral leg press, countermovement and drop jumps. Pearson`s product moment correlation and co-efficients of determination were used to explore relationships amongst all variables. Multiple regression was used to determine the combined effects of significantly correlated variables on CODS. Results. Stepwise multiple regression revealed that running speed explained 58% of the variance in CODS (F1,33=45.796, P<0.001) with the addition of eccentric knee flexor strength raising the value to 67% (F1,32=8.781, P=0.006). Conclusion. The results suggest that for basic improvements in CODS, athletes should seek to maximise their sprinting ability and enhance their eccentric knee flexor strength to allow effective neuromuscular control of the contact phase of the CODS task.